Developing and validating measurement for lean manufacturing sustenance strategies: The PLS-SEM approach - Norhana, Mohd Aripin (FIM, UMP, 2023)
Manufacturing worldwide acknowledges lean manufacturing (LM) as a tool to enhance performance. However, sustaining the implementation has been an issue for them to reap the full benefit of LM. With this issue, this study is aimed to investigate the sustaining factors for LM, develop measurement items, provide valid and reliable constructs for LM sustaining factors, and empirically validate the measuring instrument using the SEM approach. Five sustaining factors and 30 assessment items were constructed by adopting, adapting, or self-developing based on the extensive literature review. In total, 151 discrete medium and large manufacturing companies in Malaysia responded to the survey questions. Following that, the constructs were empirically assessed using the SEM model. The findings show that all of the measuring items represent their underlying constructs and contribute significantly to their respective constructs. Some limitations were identified, including the fact that this study was collected from medium and large discrete manufacturing companies in Malaysia, hence resulting in restrictions on generalizability. This research provided valuable information for practitioners to gain more understanding and develop a plan for sustaining LM implementation.